Total phenolic, flavonoid, and antioxidant capacity of bajakah (Spatholobus littoralis Hassk) - Muhammad Ikhlas Arsul; Nurfajri Syamsi; Nadila Putri; Nur Afiah Alfrianti Nur; Mukhriani; Nursalam Hamzah (Institut Teknologi Bandung, 2022)
The bajakah (Spatholobus littoralis Hassk.) is one of the typical plants from Kalimantan Island, which has potential as a drug, one of which using as an antioxidant is due to the secondary metabolites contained therein. The aims of the research are to estimate the total phenolic content, total flavonoid content, and antioxidant capacity of the bajakah by different methods. Extraction was carried out by reflux method using a solvent gradient of n-hexane, ethyl acetate, and ethanol 96%. Phenols and flavonoid content were calculated using spectroscopy. Antioxidant capacity was measured against ascorbic acid and Trolox using the CUPRAC, DPPH, and FRAP methods and reported as mg Trolox equivalent (TEAC) and ascorbic acid equivalent (AEAC) per gram extract. The ethanol extract showed the highest antioxidant capacity for the CUPRAC and FRAP methods, the n-hexane extract for the DPPH method on both varieties of bajakah tampala. Each method provides significantly different antioxidant capacity values. The CUPRAC and FRAP methods found the highest antioxidant capacity in the white variety of bajakah ethanol extract. Meanwhile, in the DPPH method, saw the highest antioxidant capacity in the red variety of n-hexane bajakah extract. DPPH and CUPRAC give a positive correlation with TPC, where CUPRAC assay produced higher values than FRAP and DPPH assays.